Design, manufacture and mechanical properties of CFRP and GFRP tubular structures via filament winding process - Prabhaharan Shroffe Jerome Ceaser Shroffe (2016)
This thesis examines the mechanical properties of CFRP (Carbon Fibre Reinforced Plastics) and GFRP (Glass Fibre Reinforced Plastics). The quest for a better energy absorbing structure or crashworthy construction has been, one of the prime areas of interest of several researchers to carry out various analytical, experimental and simulation procedures. This study aims to design, manufacture and analyse certain characteristics of such structural materials. Several types of composite materials such as C-fiber reinforced epoxy wrapped over aluminium, C-fiber reinforced bismaleimide (BMI) wrapped over aluminium, C-fiber reinforced BMI + epoxy wrapped over aluminium, E-glass fiber reinforced epoxy wrapped over aluminium have been manufactured and tested rigorously using axial and diametral compression techniques under quasi static loading. For the entire study Al 6061 liners have been chosen. Two layers were used (3x helical 55° and Ix hoop 90°). Strain data was obtained using GFLA-3-350-70 type strain gauges. Instron 5500R and Instron 8806 were used to evaluate the mechanical properties. The speed of testing was set at 1.3±0.3mm. The analysis is carried out for various combinations of matrices and reinforcements as mentioned above to study the strength of materials, to examine the response of the structure under loading; calculating some of its important properties such as yield/ultimate strength, young’s modulus etc, deviation of engineering stress from true stress and the energy absorption capability of the structures Also, a detailed analytical study on the failure modes of the various test specimens has been carried out. The novelty of this dissertation lies in the study of different combinations of composite materials, considering the key material properties needed for making superior energy absorbing structures.